Students’ Knowledge and Attitudes Concerning COVID-19: A Cross-Sectional Study: Pengetahuan dan Sikap Siswa Mengenai COVID-19: Sebuah Studi Cross-Sectional - Hussein, Wathiq Faraon (Indonesian Journal on Health Science and Medicine, 2024)
Background: The study and daily lives of Chinese undergraduate students have been significantly influenced by the COVID-19 pandemic, which has grown to be a serious public health concern. Objectives: The study aims to assess the level of students’ knowledge and attitudes concerning COVID-19. Methods: Through social networking sites and WhatsApp groups, the researcher created an electronic questionnaire that was disseminated to all Al Karma University students. The students completed it accurately. Students from Al-Karma University served as the study's participants. There were 483 people in the sample overall. The researcher uses an assessment tool to gauge the knowledge and attitudes of Al-Karma University students in Basrah regarding COVID-19. A survey was created to examine university students' COVID-19 information. Once finished, the questions were given out and shown to a group of professionals. An electronic form on the topic of the study, known as the Researcher Study Tool (Questionnaire), will be created to gather the data. There are three sections to the questionnaire. Results: The findings indicated that a greater proportion of the sample was female and that the sample's age ranged from 21 to 25 years. Students were found to have a high degree of understanding and a positive attitude toward COVID-19, with districts and sub-districts having the largest percentage of addresses. Conclusion: The majority of the female sample members were between the ages of 21 and 25, and their addresses were for the districts and sub-districts. Students were said to have a high degree of correct attitude toward COVID-19 and a good level of understanding about the virus. Highlights: Majority females (21–25 years), from districts/sub-districts in Basrah. COVID-19 knowledge assessed via electronic questionnaire for 483 students. High understanding and positive attitudes toward COVID-19 among students. Keywords: Students, Knowledge, Attitudes, COVID-19